2015
DOI: 10.1039/c5nr01125f
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the growth rate and the lifetime in carbon nanotube synthesis

Abstract: We report an inverse relationship between the carbon nanotube (CNT) growth rate and the catalyst lifetime by investigating the dependence of growth kinetics for ∼330 CNT forests on the carbon feedstock, carbon concentration, and growth temperature. We found that the increased growth temperature led to increased CNT growth rate and shortened catalyst lifetime for all carbon feedstocks, following an inverse relationship of a fairly constant maximum height. For the increased carbon concentration, the carbon feeds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 45 publications
2
29
0
Order By: Relevance
“…All studies dedicated to the investigation of the dependence of the growth rate of nanotubes on temperature reported that the rate increased nonlinearly with temperature [42,82,154155 160162 164,166168 174175 177180 183,187204]. For example, the authors of [200] found that the growth rate of nanotubes increased exponentially from 1.6 to 28 µm/min (by a factor of 18) while increasing the growth temperature from 800 to 1100 °C in the thermal CVD process using Fe as catalyst and C 2 H 2 as carbon source.…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…All studies dedicated to the investigation of the dependence of the growth rate of nanotubes on temperature reported that the rate increased nonlinearly with temperature [42,82,154155 160162 164,166168 174175 177180 183,187204]. For example, the authors of [200] found that the growth rate of nanotubes increased exponentially from 1.6 to 28 µm/min (by a factor of 18) while increasing the growth temperature from 800 to 1100 °C in the thermal CVD process using Fe as catalyst and C 2 H 2 as carbon source.…”
Section: Reviewmentioning
confidence: 99%
“…In recent reports [168,177], it was demonstrated that varying the concentration of gaseous carbon precursor in the reacting gas mixture may lead to changes of the activation energy of the nanotube growth due to switching between different growth rate-limiting processes. The authors of [177] performed the growth of MWCNTs by the laser-assisted CVD method using C 2 H 4 as carbon source (Ar and H 2 were used as gas carriers) and Fe catalyst at temperatures of 600–1000 °C.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In later research, it was clarified that for the single-walled CNTs to grow vertically at millimeter-scale height, there was a sweet spot for the size and spacing of the catalyst [11] (Fig. 10).…”
Section: Technological Development Of the Catalystmentioning
confidence: 99%